Optimizing food costs through menu engineering, portion control, supplier negotiations, waste reduction, and technology integration - Bendesa, Adinda Oktaviani; Astuti, Ni Nyoman Sri; Astawa, I Ketut; Susanto, Budi; Sarjana, I Made Bram (YAYASAN MITRA PERSADA NUSANTARA, 2022)
This study examines the implementation of food cost management in the hotel industry, identifying key factors influencing food cost stability and proposing strategies to enhance cost efficiency. Effective food cost control is crucial for maintaining profitability and sustainability in hotel operations. A mixed-methods approach was utilized, incorporating observations, documentation, and structured interviews with key personnel, including the Financial Controller, Cost Controller, Purchasing Manager, and Store Manager. Quantitative descriptive analysis revealed inefficiencies in food cost management, with excessive purchasing and insufficient sales contributing to elevated costs. Qualitative analysis further identified several internal and external factors affecting food cost stability. External influences, such as fluctuations in raw material prices, posed challenges in maintaining consistent food costs. Internally, issues such as equipment malfunctions, poor inventory management, and lack of employee discipline significantly impacted cost efficiency. Findings indicate that ineffective cost control mechanisms hinder the hotel's ability to maintain optimal food cost levels. To address these challenges, the study recommends a series of strategic interventions. Regular adjustments to menu pricing based on market trends and cost analysis can help mitigate external price fluctuations. Strengthening supervision and control over food cost disbursements will enhance accountability and efficiency. Additionally, improving employee discipline through training and performance monitoring can minimize waste and operational inefficiencies. By implementing these measures, hotels can achieve more effective food cost management, reduce unnecessary expenditures, and improve overall financial performance. Optimizing food cost efficiency not only enhances profitability but also contributes to the long-term sustainability of hotel operations. This study underscores the importance of proactive cost management strategies to ensure financial stability and operational success in the hospitality industry.